A comparison between national and transnational students' access of online learning support materials and experience of technical difficulties on a fully online distance learning master of public health programme. (2nd January 2017) - Gemmell, Isla; Harrison, Roger
Abstract: Online distance learning (ODL) is now recognised as a mainstream teaching method for undergraduate and postgraduate students around the world. However, differences in learner characteristics such as help-seeking behaviour between transnational students and home students may impact on student attainment. 64 students undertaking an online master of public health programme in the UK completed a survey which explored students' access of learner support resources, their experience of technical difficulties, demographic characteristics and learner characteristics. We collected data on the geographic region in which students were currently living and their geographical region of origin. Students whose region of origin was outside the UK/EU accessed a greater number of support resources than students based within the UK/EU and students whose region of residence was outside the UK/EU experienced a greater number of technical difficulties than students from within the UK/EU. Thus transnational students access more support resources than home students despite having to overcome more technical difficulties in order to do so. The classification of students based on fee-paying status was unable to detect these differences and may not be appropriate for ODL courses.